Notch signalling in T cells: bridging tumour immunity and intratumoral cellular crosstalk - Sultana, Jasmine; Choudhury, Pritha Roy; Bera, Saurav; Chakravarti, Mohona; Guha, Aishwarya; Das, Prodipto; Das, Juhina; Iyer, Gayatri S; Sarkar, Anirban; Dhar, Sukanya; Ganguly, Nilanjan; Baral, Rathindranath; et al. (Frontiers in Immunology, 2025)
BackgroundNotch receptor–ligand interaction is ubiquitous and fundamental for coordinating cellular differentiation and determining cell fate for the development of various tissues and organs. Aberrant mutations in the Notch cascade result in various pathophysiological disorders, including cancer. Diverse aspects of carcinogenesis regulated by Notch include the shaping of anti-tumour T-cell immunity through antigen-presenting cell (APC)–T cell interaction and effector functions.Chief contentNotch depends on juxtacrine and paracrine signalling to influence intercellular communications in the tumour microenvironment. Several preclinical and clinical studies have revealed Notch as a bi-effector molecule, which has a differential effect depending on the immune contexture of the tumour microenvironment. The Notch cascade serves as an effective therapeutic target in preventing off-target cell death and promoting tumour-specific T-cell priming.ConclusionThis review revolves around Notch crosstalk with respect to the interaction between T-cell populations and other intratumoral cellular components, including professional antigen-presenting cells like dendritic cells, macrophages, B cells, immunosuppressive myeloid-derived suppressor cells, and cancer stem cells. It also summarizes the impact of targeting Notch signalling within intratumoral T cells in combination with traditional oncotherapies.